THE ENHANCEMENT OF FORMULATING HYPOTHESES AND INFERRING SKILLS IN COLLOIDAL CONCEPT BY PROBLEM SOLVING LEARNING MODEL - Anggun Sari Nurulita; Noor Fadiawati; Chansyanah Diawati (Universitas Lampung, 2012)
This research was to describe the effectiveness of problem solving learning model to enhance formulating hypotheses and inferring skills in colloidal concept. Students who became the subject of this research was XI grade of Science 4 YP Unila Senior High School in Bandar Lampung Academic Year 2011/2012. This research used the pre-experimental method and one group pretest-posttest design. The effectiveness of problem solving learning model was determined based on the average value of n-Gain. The results of this research showed that the average value of n-Gain of formulating hypotheses and inferring skills were 0.54 and 0.67. If they were interpreted, both of them were included in medium category. Thus, it can be concluded that the problem solving learning model effective to enhance formulating hypotheses and inferring skills in colloidal concept in medium category.Penelitian ini bertujuan untuk mendeskripsikan peningkatan keterampilan merumuskan hipotesis dan menarik kesimpulan pada materi koloid. Yang menjadi subjek penelitian adalah siswa kelas XI IPA 4 SMA YP Unila Bandar Lampung tahun ajaran 2011/2012. Penelitian ini menggunakan metode preksperimen dengan desain One Group Pretest-Posttest. Efektivitas model pembelajaran problem solvingditentukan berdasarkan rerata n-Gain. Hasil penelitian menunjukkan bahwa rerata n-Gain kemampuan merumuskan hipotesis dan menarik kesimpulan adalah sebesar 0,54 dan 0,67. Keduanya berada dalam kategori medium. Sehingga dapat disimpulkan bahwa model pembelajaran problem solving efektif untuk meningkatkan keterampilan merumuskan hipotesis dan menarik kesimpulan.Kata kunci: keterampilan merumuskan hipotesis, keterampilan menarik kesimpulan, problem solving